TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE IN TEACHING ANALYTICAL EXPOSITION TEXT FOR 11TH GRADE AT KESUMA INDAH PADANG SIDIMPUAN SENIOR HIGH SCHOOL - Cloudya Sihombing; Nora Ronita Dewi (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
The objectives of the study were to find out the components of TPACK in teaching analytical exposition text and to reveal how the TPACK is implemented in teaching analytical exposition text for students. The study was conducted by using descriptive qualitative method which investigated an English teacher and students at grade 11th as the subject of the research. The techniques of collecting the data were observation, video recording, and interview. The results of the study showed that the components of TPACK as proposed by Mishra and Koehler (2006) such as content knowledge (CK), pedagogical knowledge (PK), pedagogical content knowledge (PCK), technological knowledge (TK), technological content knowledge (TCK), technological pedagogical knowledge (TPK), and technological pedagogical content knowledge (TPACK) were found in teaching analytical exposition text. It is also found that the implementation of TPACK as suggested by Harris and Hofer (2009), was conducted through five basic process, such as (1)determining the goals of the learning, (2) choosing the most appropriate methods as well as strategies that can be used to enhance students’ learning experience, (3) selecting and sequencing what kind of activities that students will engage in during the learning, (4) determining how students can be assessed based on the learning goals and their achievement, and (5) selecting what kind of tools and resources will be used to help students achieve the learning goals.Keywords: TPACK, analytical exposition text, teaching writing